2018
DOI: 10.3168/jds.2017-13797
|View full text |Cite
|
Sign up to set email alerts
|

Fermentation and aerobic stability of rehydrated corn grain silage treated with different doses of Lactobacillus buchneri or a combination of Lactobacillus plantarum and Pediococcus acidilactici

Abstract: We investigated the effects of different types and doses of inoculants for ensiling rehydrated corn grain. Shelled corn was finely ground and rehydrated to 35% moisture. Treatments were as follows: (1) control (no additives); (2) Lactobacillus plantarum and Pediococcus acidilactici (LPPA) at a theoretical application rate of 1 × 10 cfu/g; (3) LPPA at 5 × 10 cfu/g; (4) LPPA at 1 × 10 cfu/g; (5) Lactobacillus buchneri (LB) at 1 × 10 cfu/g; (6) LB at 5 × 10 cfu/g; and (7) LB at 1 × 10 cfu/g. We detected no effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
37
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 28 publications
7
37
2
Order By: Relevance
“…The values obtained in this experiment are very close to those found by Andrade Filho et al (2010), who evaluated three levels of reconstitution in the ensilage of dry corn grains, obtaining gas-loss values of 1.91, 1.80 and 1.70% for 20, 30 and 40% of moisture, respectively. In rehydrated corn grain silage at 124 days of fermentation, Silva et al (2018) also verified values close of this experiment (1,65 % DM).…”
Section: Resultssupporting
confidence: 86%
“…The values obtained in this experiment are very close to those found by Andrade Filho et al (2010), who evaluated three levels of reconstitution in the ensilage of dry corn grains, obtaining gas-loss values of 1.91, 1.80 and 1.70% for 20, 30 and 40% of moisture, respectively. In rehydrated corn grain silage at 124 days of fermentation, Silva et al (2018) also verified values close of this experiment (1,65 % DM).…”
Section: Resultssupporting
confidence: 86%
“…Fermentative DM losses in silage are primarily a result of carbon dioxide production (Borreani et al, 2018). Losses observed in this study fell within the range of those reported in the literature, where either corn grain or corn silage was fermented in laboratory-scale silos (Kleinschmit and Kung, 2006;Schmidt and Kung, 2010;Tabacco et al, 2011;da Silva et al, 2018). Greater DM losses with LBLL can most likely be attributed to the production of carbon dioxide when lactic acid is converted to acetic acid by L. buchneri LB1819 (Oude Elferink et al, 2001).…”
Section: Resultssupporting
confidence: 74%
“…The reasons for differences among studies might be related to maize hybrid, management, particle size, moisture content and packing density. da Silva et al (2018) ensiled rehydrated maize with 350 g/kg moisture at 1085 kg/m 3 density and found only 628 g/kg DM at 124 days after ensiling, evidencing greater effluent losses than reported in previously mentioned studies.…”
Section: Discussionmentioning
confidence: 51%